Development of Trading Agent Using MQL4 Language - Božović, Mihailo; Leskovar, Robert; Werber, Borut (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The thesis deals with the development of a trading agent using the MQL4 language, specific for trading on the MetaTrader 4 platform. Our goal was to create a prototype of an agent that would independently analyze price movements among the most important currency pairs and execute trades based on a specific strategy. We implemented functions in MQL4 that allow the agent to make decisions about buying and selling currency pairs based on various indicators and price movement analyses. The research also included testing and optimizing performance in simulated trades. The existing literature mainly focuses on theoretical aspects of algorithmic trading, but there is often a lack of concrete case studies and practical implementations in MQL4. Also, many studies are focused on general trading strategies and functions, while there is less emphasis on the adaptability of algorithms to specific market conditions and the impact of various optimization techniques on their long-term performance.